KEPATUHAN PEMBATASAN ASUPAN CAIRAN TERHADAP LAMA MENJALANI HEMODIALISA - Anita, Diyah Candra; Novitasari, Dwi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
One of the treatments to save the life of patients with chronic renal failure is hemodialysis therapy, accompanied by fluid intake restriction. The absence of this restriction will lead to accumulated fluid which can result in edema around the body. This condition may cause increased blood pressure and aggravated heart work. In addition, asphyxia can also occur due to the accumulated fluid. This research aimed to figure out the differences and the correlation between hemodialysis patients obedience towards fluid intake restriction and the continuation of hemodialysis experience in PKU Muhammadiyah Yogyakarta. This research was a descriptive- quantitative study applying cross sectional method. Samples were chosen using accidental sampling technique, involving 60 respondents. The instruments used in this research were questionnaires and patients medical records. Data were analyzed using Spearman Rank correlation formula and Kruskall Wallis test. The results of this research showed that there was a correlation with p=0,033, but the difference was not statistically significant (p=0,088) between the continuatio of hemodialysis treatment and the patients obedience towards fluid intake restriction. In conclusion, the longer time the patients experienced hemodialysis therapy, the less obedience they had in restricting the fluid intake. Keywords: Obedience, fluid, chronic renal failure, hemodialysis